Conflict, security and development an introduction - Jackson, Paul; Beswick, Danielle (Routledge, Taylor & Francis Group, 2018)
This textbook draws on academic theory, field research and policy developments to provide an overview of the connections between security and development, before, during and after conflict. The authors are experienced in both the theory and the practice of this field, and illustrate the links between conflict, security and development with practical examples, drawing on key case studies from the past twenty years. Each chapter is informed by student pedagogy and the book will be essential reading for all students of development studies, war and conflict studies, and human security and is recommended for students of international security and IR in general.